Implementasi Reservasi Kamar Berbasis Web Pada Hotel Bintang Wisata Pantai Galesong Kabupaten Takalar - Nurhaedar; Lina Mariana (STMIK Amika Soppeng, 2022)
Room availability information at the Bintang hotel on galesong tourist beach is still manual can only be obtained directly through the receptionist, The room booking transaction fee is still calculated manually, The making of the memorandum is written on paper. The creation of reports is carried out by copying one by one the order data, so that sometimes errors occur in the reporting of transaction information that is irrelevant, accurate and timely. The purpose of this study is to build and implement a web-based Room Reservation system at the Galesong Beach Tourism Star Hotel, Takalar Regency with the research methods used, namely System problem analysis and Waterfall model system development, UML model software engineering design, system database Using MSQL, Php coding, system testing with a Black Box approach. The result of this study is to implement a web-based room reservation information system at the Bintang Galesong Beach Tourism Hotel, Takalar Regency. Providing convenience, namely 1) tourists to find out information and room resevation online 2) the admin presents accurate, relevant and timely information about the availability of lodging rooms and processes room reservation data at the Bintang Galesong Beach Tourism Hotel, Takalar Regency.